Impact of Industrial BOTS on Employment, Skilled-Unskilled Wage Disparities and Talent Gap - Roy, Shreya (Journal of Quantitative Economics, 2024)
This paper investigates the impacts of industrial robots (BOTs) on the employment of skilled and unskilled labour within the manufacturing sector. We employ an empirical approach to analyse the data and complement the empirical findings with a theoretical
Keywords: Industrial Robots; Skilled Unskilled Wage Gap; Talent Gap; General Equilibrium